Comparison of genetic services with and without genetic registers: knowledge, adjustment, and attitudes about genetic counselling among probands referred to three genetic clinics. Issue 12 (1st December 2002) - Wright, C; Kerzin-Storrar, L; Williamson, P R; Fryer, A; Njindou, A; Quarrell, O; Donnai, D; Craufurd, D
Abstract : Genetic register services incorporating long term follow up and a proactive approach to at risk subjects have been recommended as a way of improving access to genetic counselling for families with dominant or X linked genetic disorders and chromosome translocations. The aims of the present study were to evaluate the psychosocial benefits and drawbacks of long term family contact, and to evaluate the attitudes of probands and their general practitioners towards proactive genetic counselling. We interviewed 192 people referred to three regional genetic clinics because of a family history of Duchenne or Becker muscular dystrophy, myotonic dystrophy, or chromosome translocations, and 43 of the referring GPs. Probands attending the centre using a genetic register approach were compared with those from the two centres offering the standard clinical genetic service. A very high proportion of probands in both groups were well informed about the genetic risks to themselves and their children, were satisfied with the service they had received from their local genetic clinic, and felt adequately prepared to discuss the family illness with their children. The register probands expressed approval of the ongoing contact and open access provided by the register service. Asked whether previously unaware relatives should be informed of their at risk status, 98% (188/192) said it was acceptable for this information to be disclosed by a family member, while three quarters of the probands (149/192) and just over half the GPs (27/43) thought it acceptable for the genetic service to approach them; a similar proportion of both GPs and probands also found it acceptable for GPs to do so. More than half the probands (107/190) thought it was the family's responsibility to pass on genetic risk information, but 43% said that either the genetic service or the GP should be responsible for this. The findings show that the genetic register approach incorporating long term follow up and a proactive approach to genetic counselling is highly acceptable to the families concerned, and although the register and non-register probands did not differ significantly on any of the main outcome measures used in this relatively short term study, it may be that the continuing contact associated with the register approach offers long term benefits, especially for those genetic conditions where medical surveillance may have an impact on the prognosis.